A comparative study on registration system of real estate between Hong Kong and Mainland China. Issue 1 (19th February 2018) - Wang, Hao; Wei, Shuyan; Tang, Bo-sin; Chen, Junhua; Li, Wenbin
Abstract : Purpose: The purpose of this paper is to review land/real estate registration practice in Hong Kong, and make an in-depth comparison with Mainland China and finally provide helpful suggestions for the government. Design/methodology/approach: Research methods including document analysis/review and comparative study are used in this paper. Findings: The main findings focus on the problems existing in the mainland, including narrow query subject, single way of query, limited query time, and lacking of incentive mechanism. Helpful suggestions for real estate registration system in Mainland China are offered based on the comparative study. Practical implications: The unified registration system can improve the efficiency of administrative institutions to ensure an open and transparent environment of property right registration, which helps prevent the relevant departments from abusing administrative power and harming the interests of obligees. The findings of this research can serve as a useful reference for policy makers to improve the unified registration system in China. Originality/value: The registration system/mechanism determines the efficiency and effectiveness of real estate/land market. However, land registration and query in some countries such as Mainland China have institutional problems which hinder the sustained and healthy development of the real estate industry. The value of this paper is to propose constructive suggestions for such countries/regions by comparing and learning from a good model.